2011
DOI: 10.4314/sjms.v6i2.72451
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of HBV Risks and Hepatitis B Vaccination Status Among Health Care Workers at Khartoum and Omdurman Teaching Hospitals of Khartoum State in Sudan

Abstract: HBV infection is notorious and is endemic in Sudan. Health care workers are at particular increased risk for the infection. Their knowledge and acceptance of vaccination against the virus is of at most importance for the control of the disease. Objective: To study the knowledge and vaccination status among health care workers in some central hospitals in Sudan. Methodology: Data from different categories of health workers were collected using structure questionnaire after taking informed consent. Data were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
3
2
Order By: Relevance
“…However, compared to a previous study published in 2011 [11], there was a significant improvement in the vaccination status among HCWs; 26.19% in the previous study compared with 72.6% in the present study.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…However, compared to a previous study published in 2011 [11], there was a significant improvement in the vaccination status among HCWs; 26.19% in the previous study compared with 72.6% in the present study.…”
Section: Discussioncontrasting
confidence: 91%
“…Our study showed that the majority of respondents who do not wear gloves when they are dealing with patients were doctors (representing 12.6% out of the total number of doctors), which is similar to a study carried out in Wad Madani-Sudan [11]. That study showed that 10.4% of doctors did not wear gloves when they deal with patients, and this is a dangerous indicator of careless practice towards this disease.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…High (Yemen and Sudan) or low (Saudi Arabia or Turkey) prevalence of HBsAg may refers to equity in access to health care in some EMRO/Middle East countries. For example, one study showed that the status of Hepatitis B vaccination wasn't acceptable between a group of HCWs in Sudan and only less than one third of them had received all doses of vaccine,[94] while the other study in Saudi Arabia revealed that more than 70% of HCWs received HBV vaccine. [95]…”
Section: Discussionmentioning
confidence: 99%
“…Hence, Sudanese healthcare professionals are no exception when it comes to exposure to the common medical OHS hazards. Gadour and Abdullah [34] investigated the level of knowledge on the hepatitis B virus (HBV) among health care workers in public teaching hospitals in Khartoum, Sudan. The findings revealed that workers had very high knowledge about HBV, although the study observed that low levels of immunity against the virus existed among the staff.…”
Section: Current Status Of Ohs Research In Sudanmentioning
confidence: 99%